2001
DOI: 10.4049/jimmunol.166.3.2141
|View full text |Cite
|
Sign up to set email alerts
|

Deficient IL-12(p35) Gene Expression by Dendritic Cells Derived from Neonatal Monocytes

Abstract: To gain insight into the defects responsible for impaired Th1 responses in human newborns, we analyzed the production of cytokines by dendritic cells (DC) derived from cord blood monocytes. We observed that neonatal DC generated from adherent cord blood mononuclear cells cultured for 6 days in the presence of IL-4 and GM-CSF show a phenotype similar to adult DC generated from adherent PBMC, although they express lower levels of HLA-DR, CD80, and CD40. Measurement of cytokine levels produced by neonatal DC upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
234
2
6

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 322 publications
(270 citation statements)
references
References 27 publications
(18 reference statements)
26
234
2
6
Order By: Relevance
“…Several groups have demonstrated that DC from both human cord-blood [50], and neonatal mice [51] show decreased capacity of antigen presentation and stimulation of CD4 + T cells. An impaired function of human neonatal DC is dependent on their reduced ability to produce IL-12 [52], which is one explanation for the Th2 bias of neonatal T cell responses, as IL-12 plays a crucial role in promoting Th1 development by inducing IFN-c production by Th1 cells and NK cells [53]. Despite the limitations of the immune system in early life, successful pediatric vaccines exist.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have demonstrated that DC from both human cord-blood [50], and neonatal mice [51] show decreased capacity of antigen presentation and stimulation of CD4 + T cells. An impaired function of human neonatal DC is dependent on their reduced ability to produce IL-12 [52], which is one explanation for the Th2 bias of neonatal T cell responses, as IL-12 plays a crucial role in promoting Th1 development by inducing IFN-c production by Th1 cells and NK cells [53]. Despite the limitations of the immune system in early life, successful pediatric vaccines exist.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of monocyte-derived DC DC were generated from peripheral blood mononuclear cells (PBMC) obtained from healthy donors as previously described [43]. After 6 days, nonadherent cells corresponding to DCenriched fraction routinely contained more than 95% of DC as assessed by morphological and FACS analysis as described earlier [43].…”
Section: Methodsmentioning
confidence: 99%
“…After 6 days, nonadherent cells corresponding to DCenriched fraction routinely contained more than 95% of DC as assessed by morphological and FACS analysis as described earlier [43].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early immunization is required to impact on this mortality, but the development of vaccines that are effective at birth is impeded by the immaturity of the immune system. [3][4][5] The antibody (Ab) responses to T-cell-independent and many T-celldependent vaccine antigens are lower in young infants when compared to older children or adults. [6][7][8][9][10] Qualitative differences in Ab responses in infants include reduced Ab avidity and repertoire, and different immunoglobulin G (IgG) subclass distribution.…”
Section: Introductionmentioning
confidence: 99%